Penerapan Penggunaan Telehealth terhadap Kepuasan Ibu Hamil pada Masa Pandemi Covid-19 : A Systematic Review - Iva Satya Ratnasari; Indah Rahmaningtyas; Finta Isti Kundarti (Poltekkes Kemenkes Maluku, 2022)
The COVID-19 pandemic has led to a decrease pregnant women visit to health services and changes in health care. Various midwifery services have been developed using telehealth. The purpose of this study was to 2022. Results: 11 articles met the inclusion criteria. The research were conducted in United States, England, Japan, and Zimbabwe. The use of telehealth for pregnant women during the COVID-19 analyze the effect of using telehealth on the satisfaction of pregnant women during the COVID-19 pandemic through systematic review study. The method was to search through Pubmed, ProQuest, Science Direct, and Wiley Library databases with the publication year from December 2019 to January pandemic resulted in high satisfaction and appeared in 10 articles. Only 1 article resulted in lower satisfaction. Telehealth in the future will be very useful and become an innovation in the field of obstetrics, especially to provide pregnancy care even after the COVID-19 pandemic ends. Although the use of telehealth still has limitations in physical examination, it can be used as an adjunct and complement to in-person visits. Further research can be conducted to develop research on the factors that influence the satisfaction of implementing telehealth in pregnant women.